Gender-Specific Effect of -102G>A Polymorphism in Insulin Induced Gene 2 on Obesity in Chinese Children - Fang-Hong Liu; Jie-Yun Song; Yi-Ning Zhang; Jun Ma; Hai-Jun Wang (International Journal of Endocrinology)
Background. Insulin induced gene 2 (INSIG2) encodes a protein that has a biological effect on regulation of adipocyte metabolism and body weight. This study aimed to investigate the association of INSIG2 gene -102G>A polymorphism with obesity related phenotypes in Chinese children and test gender-specific effects. Methods. The 2,030 independent individuals aged from 7 to 18 years, including 705 obese cases and 1,325 nonobese controls, were recruited from local schools. We measured the obesity-related phenotypes and detected the serum lipids. We genotype -102G>A polymorphism by using the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Results. In all individuals, we found that the GG/GA genotype of INSIG2 -102G>A polymorphism was associated with risk of severe obesity (OR = 1.62, 95% CI: 1.11–2.36, and P=0.012) under the dominant model. The association with severe obesity existed only in boys (OR = 1.91, 95% CI: 1.15–3.17, P=0.012). The GG/GA genotype of -102G>A polymorphism was also associated with higher waist circumference (β=2.61 cm, P=0.031) in boys. No similar association was found in girls. The polymorphism was not associated with other obesity-related phenotypes, neither in all individuals nor in gender-specific population. Conclusions. This study identified a gender-specific effect of INSIG2 -102G>A polymorphism on risk of severe obesity and waist circumference in Chinese boys.